Wsparcie Kościoła i przeciwdziałanie skutkom bezrobocia w okresie przemian ustrojowych w Polsce - Wojtala, Marcin (Studia Pastoralne, 2020)
In the most recent history of Poland, the beginning of the 90s was undoubtedly a breakthrough. In 1989, communism started falling apart and the new reality that emerged showed that the upcoming change would not be easy and would have, at least at the beginning, a negative impact on social life and the economy. In a country dominated by old-fashioned agriculture, hyperinflation, enormous debt and a devastated economy, it was extremely difficult to introduce elements of private property and free market economy. The biggest economic distress related to the transformation was the phenomenon of unemployment, the extent of which was so vast that material status of Poles and their families deteriorated very quickly. It implied such negative phenomena as poverty, helplessness, social isolation, and emotional issues in families. Many people did not cope in the situation of rivalry and competition. At the same time, old habits, disparities and financial deficiency worsened the psychological problems of individuals. The Catholic Church, recognising the extent of the problem, got involved in supporting families of the unemployed. The Church preached the teaching based on the value of human labour, human dignity, the need of social justice, and interpersonal solidarity. She agitated for national debate on unemployment to take remedial measures. Help provided by the Church, and charitable institutions and foundations related to the Church to families of the unemployed should not be underestimated. The role of the Church in Poland during this difficult transitional period should be remembered.